2005
DOI: 10.1093/annonc/mdi150
|View full text |Cite
|
Sign up to set email alerts
|

Worse survival for TP53 (p53)-mutated breast cancer patients receiving adjuvant CMF

Abstract: Background: TP53 has been described as a prognostic factor in many malignancies, including breast cancer. Whether it also might be a predictive factor with reference to chemo-and endocrine therapy is more controversial. Patients and methods: We investigated relapse-free (RFS), breast cancer-corrected (BCCS) and overall survival (OS) related to TP53 status in node-positive breast cancer patients that had received polychemotherapy [cyclophosphamide, methotrexate, 5-fluorouracil (CMF)] and/or endocrine therapy (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 26 publications
4
34
1
Order By: Relevance
“…TP53 mutation is one of the most common genetic abnormalities in breast cancer (40,41) and associates with more aggressive disease and a poor clinical outcome (40)(41)(42)(43). Although the overall frequency of TP53 mutation is 20%-30%, the incidence is much higher in certain breast cancer subtypes.…”
Section: Figurementioning
confidence: 99%
“…TP53 mutation is one of the most common genetic abnormalities in breast cancer (40,41) and associates with more aggressive disease and a poor clinical outcome (40)(41)(42)(43). Although the overall frequency of TP53 mutation is 20%-30%, the incidence is much higher in certain breast cancer subtypes.…”
Section: Figurementioning
confidence: 99%
“…Wild-type p53 is a tumour suppressor protein and plays an essential role in regulating genomic stability by controlling the cell cycle and inducing apoptosis when cell damage cannot be repaired [65][66][67] . In normal cells, p53 has a very short half-life due to ubiquitylation and proteasome degradation [68,69] . IHC can be used, as wild-type p53 protein is rapidly degraded, while TP53 mutations (18%-25% of primary breast carcinomas) are often associated with the production of a stable protein.…”
Section: Markers Of Apoptosis and Cell Proliferation: Ki-67 Proliferamentioning
confidence: 99%
“…Andersson et al [62] found that TP53 mutations (assessed by sequencing) might induce resistance to cyclophosphamide, methotrexate, 5-fluorouracil adjuvant treatment.…”
Section: Non-anthracycline Chemotherapy In Vivomentioning
confidence: 99%